Toward a theory for diversity gradients: the abundance–adaptation hypothesis. Issue 2 (13th April 2017) - Weiser, Michael D.; Michaletz, Sean T.; Buzzard, Vanessa; Deng, Ye; He, Zhili; Shen, Lina; Enquist, Brian J.; Waide, Robert B.; Zhou, Jizhong; Kaspari, Michael
Abstract : The abundance–adaptation hypothesis argues that taxa with more individuals and faster generation times will have more evolutionary 'experiments' allowing expansion into, and diversification within, novel habitats. Thus, as older taxa have produced more individuals over time, and smaller taxa have higher population sizes and faster generation times, the Latitudinal Diversity Gradients (LDGs) of these clades should show shallower slopes. We describe the LDGs for archaea, bacteria, fungi, invertebrates and trees from six North American forests. For three focal groups – bacteria, ants, and trees – older taxa had shallower LDG slopes than the more recent, terminal taxa. Across 12 orders of magnitude of body mass, LDG slopes were steeper in larger taxa. The slopes of LDGs vary systematically with body size and clade age, underscoring the non‐canonical nature of LDGs. The steepest LDG slopes were found for the largest organisms while the smallest, from bacteria to small litter‐soil invertebrates, have shallower‐ to zero‐slope LDGs. If tropical niche conservatism is the failure of clades to adapt to, and diversify in temperate habitats, then the steep LDGs of chordates and plants likely arise from the decreased ability of clades with large individuals to adapt to the multiple challenges of extra‐tropical life.